Analisis Penerimaan Teknologi E-retribusi Pasar dengan Pendekatan Theory of Reasoned Action - Magdalena, Maria; Sediyono, Eko; Marwata, Marwata (Universitas Diponegoro, 2018)
The Trade Service The Salatiga City Government applies non-cash market retribution (market e-retribution) in improving the quality of services that are transparent and accountable in traditional markets. Given that there has been no research discussing the acceptance of market e-retribution technology, this issue can be an interesting topic to study. Theory of Reasoned Action (TRA) is used as a conceptual model in this study with the aim of investigating the factors that influence the acceptance of market e-retribution technology in traditional market traders in the city of Salatiga. The results of this study indicate that perceptions of usefulness, perception of self-efficacy and subjective norms have a positive effect, but are not statistically significant, while perceptions of compatibility and attitude have a positive and statistically significant effect